BcWRKY22 Activates BcCAT2 to Enhance Catalase (CAT) Activity and Reduce Hydrogen Peroxide (H2O2) Accumulation, Promoting Thermotolerance in Non-Heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Haiyan Wang; Zhanyuan Gao; Xiaoshan Chen; Entong Li; Ying Li; Changwei Zhang; Xilin Hou (Antioxidants, 2023)
WRKY transcription factors (TFs) participate in plant defense mechanisms against biological and abiotic stresses. However, their regulatory role in heat resistance is still unclear in non-heading Chinese cabbage. Here, we identified the WRKY-IIe gene BcWRKY22(BraC09g001080.1), which is activated under high temperatures and plays an active role in regulating thermal stability, through transcriptome analysis. We further discovered that the BcWRKY22 protein is located in the nucleus and demonstrates transactivation activity in both the yeast and plant. Additionally, our studies showed that the transient overexpression of BcWRKY22 in non-heading Chinese cabbage activates the expression of catalase 2 (BcCAT2), enhances CAT enzyme activity, and reduces Hydrogen Peroxide (H2O2) accumulation under heat stress conditions. In addition, compared to its wild-type (WT) counterparts, Arabidopsis thaliana heterologously overexpresses BcWRKY22, improving thermotolerance. When the BcWRKY22 transgenic root was obtained, under heat stress, the accumulation of H2O2 was reduced, while the expression of catalase 2 (BcCAT2) was upregulated, thereby enhancing CAT enzyme activity. Further analysis revealed that BcWRKY22 directly activates the expression of BcCAT2 (BraC08g016240.1) by binding to the W-box element distributed within the promoter region of BcCAT2. Collectively, our findings suggest that BcWRKY22 may serve as a novel regulator of the heat stress response in non-heading Chinese cabbage, actively contributing to the establishment of thermal tolerance by upregulating catalase (CAT) activity and downregulating H2O2 accumulation via BcCAT2 expression.